IMPLEMENTASI STRATEGI GURU AKIDAH AKHLAK DALAM MENINGKATKAN KEDISIPLINAN PADA PESERTA DIDIK DI ERA DIGITAL - Himatul’Ulya; Andini Latifatun Nisa; Mar’atus Sholihah; Achmad Wafa Husni M; Ainin Naim (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The rapid development of digital technology has significantly influenced students' behavior and character, particularly in terms of discipline. Easy access to various digital platforms provides opportunities to enhance the quality of learning; however, it also presents challenges, such as decreased compliance with school regulations, reduced learning responsibility, and increased distractions during the learning process. Therefore, Aqidah Akhlak teachers play a strategic role in fostering students' disciplinary character through various approaches that are relevant to contemporary educational developments. This article aims to describe the implementation of Aqidah Akhlak teachers' strategies in improving students' discipline in the digital era. This study employs a library research approach by reviewing relevant national journal articles published between 2020 and 2026. The findings indicate that the strategies implemented by teachers include role modeling, habituation of disciplined behavior, providing advice, applying reward and punishment, strengthening character education, and utilizing digital media as a learning tool. The implementation of these strategies has been shown to enhance students' awareness of complying with school regulations, taking responsibility for academic tasks, and using digital technology more wisely. The successful implementation of these strategies is supported by strong collaboration among teachers, schools, and parents in providing continuous guidance.